Analisis Prinsip Non-Interference Dalam Asean Way: Implikasi Bagi Stabilitas Ekonomi-Keamanan Di Asia Tenggara - Laia, Anastasia Meilin Gita Permata; Zeffilda, Gadis (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2025)
This research examines the principle of non-interference in the ASEAN Way and its implications for economic stability and security in Southeast Asia. As a cornerstone of ASEAN, this principle aims to maintain regional harmony by respecting the sovereignty of member states. However, its implementation faces challenges, particularly in addressing transnational issues such as economic integration through the ASEAN Economic Community (AEC) and the South China Sea disputes. The study adopts a constructivist approach and two-level game theory to analyze how domestic and international dynamics influence the effectiveness of this principle. The findings indicate that the non-interference principle creates a dilemma between preserving national sovereignty and the need to strengthen regional cooperation. In the context of the AEC, differences in economic development levels among member states often hinder policy harmonization in trade. Meanwhile, the South China Sea disputes highlight ASEAN’s limitations in confronting external aggression, although consensus-building and quiet diplomacy have helped maintain internal solidarity. The principle also slows decision-making on urgent strategic issues. The study recommends that ASEAN adapt its application of the non-interference principle to be more responsive to contemporary challenges. A more flexible approach and robust enforcement mechanisms are necessary to enhance the effectiveness of regional policies. By strengthening collective identity and regional norms, ASEAN can bolster regional stability, improve economic competitiveness, and respond to global challenges more effectively and sustainably. Keywords: ASEAN Way, AEC, SCS, Two-Level Game Theory ABSTRAK Penelitian ini mengkaji prinsip non-interference dalam ASEAN Way dan implikasinya terhadap stabilitas ekonomi serta keamanan di Asia Tenggara. Sebagai pilar utama, prinsip ini bertujuan menjaga keharmonisan regional dengan menghormati kedaulatan negara anggota. Namun, penerapannya menghadapi tantangan, terutama dalam menangani isu-isu transnasional seperti integrasi ekonomi melalui ASEAN Economic Community (AEC) dan sengketa Laut Cina Selatan. Penelitian ini menggunakan pendekatan konstruktivisme dan two-level game theory untuk menganalisis bagaimana dinamika domestik dan internasional memengaruhi efektivitas penerapan prinsip ini. Hasil penelitian menunjukkan bahwa prinsip non-interference menciptakan dilema antara menjaga kedaulatan nasional dan kebutuhan untuk memperkuat kerja sama regional. Dalam konteks AEC, perbedaan tingkat pembangunan ekonomi antarnegara anggota sering menghambat harmonisasi kebijakan perdagangan. Sementara itu, sengketa Laut Cina Selatan menyoroti keterbatasan ASEAN dalam menghadapi agresi eksternal, meskipun pendekatan konsensus dan diplomasi tenang membantu menjaga solidaritas internal. Prinsip ini juga memperlambat proses pengambilan keputusan pada isu strategis yang mendesak. Penelitian ini merekomendasikan ASEAN untuk mengadaptasi penerapan prinsip non-interference agar lebih responsif terhadap tantangan kontemporer. Pendekatan yang lebih fleksibel dan mekanisme penegakan yang kuat diperlukan untuk meningkatkan efektivitas kebijakan regional. Dengan memperkuat identitas kolektif dan norma-norma regional, ASEAN dapat memperkuat stabilitas kawasan, meningkatkan daya saing ekonomi, serta menghadapi tantangan global secara lebih responsif dan berkelanjutan. Kata kunci: ASEAN Way, AEC, SCS, Two-Level Game Theory